Analysis of the Effectiveness of the Campus Teaching Program Batch 7 in Improving the Quality of Learning in Elementary Schools - Septyana Prasetianingrum; Khusnul Khotimah; Siti Mariani Basannang; Yendra; Adriani Lande; Darmayanti, Novi; Mochammad Taqiyyuddin (PT. Global World Scientific, 2025)
The Campus Teaching Program Batch 7 has made significant contributions to improving the quality of education at SDN Siman, particularly in literacy, numeracy, and student learning motivation. With an experiential learning approach, student participants in the program provide innovative mentoring that helps overcome the challenges of basic education in areas with limited facilities. This program not only has an impact on students, but also on improving teacher competence, school community collaboration, and strengthening synergy between the community and educational institutions. However, the implementation of the program is not without challenges, such as limited internet connectivity and the diversity of programs that affect the focus of learning. Recommended solutions include the provision of offline modules, contextual training for teachers, and the use of impact matrices to increase the effectiveness of interventions. By integrating experiential and service-based learning, this program has the potential to become a model for educational transformation in areas with limited infrastructure.